Effects of Dental Rehabilitation under General Anesthesia on Children’s Oral Health-Related Quality of Life Using Proxy Short Versions of OHRQoL Instruments - Ziad D. Baghdadi (The Scientific World Journal)
Aim. To examine the impact of comprehensive dental treatment under general anesthesia (GA) on oral health-related quality of life (OHRQoL) in children using short form versions of the Parental-Caregivers Perceptions questionnaire (P-CPQ) and Family Impact Scale (FIS). Design. A pretest/posttest study involved parents whose children (N = 67) were affected with severe childhood caries and completed comprehensive dental treatment under GA. All parents completed the short form versions of the P-CPQ and FIS at baseline and 4–8 weeks following the dental treatment. To examine test-retest reliability, a convenience sample of 38 parents repeated the pretreatment questionnaires 1-2 weeks after they completed them at baseline. Statistical tests including the Kruskal-Wallis test, Cronbach’s alpha, and paired t-test were used to examine cross-sectional construct validity, internal consistency, and responsiveness of the instruments, respectively. Results. Cross-sectional construct validity and internal consistency were acceptable. Test-retest reliability was excellent. Large decreases in posttreatment scores were observed along with moderate to large effect sizes. Conclusions. Dental treatment under GA is associated with considerable improvement in OHRQoL of children and their families, as demonstrated by short form versions of the P-CPQ and FIS completed by the children’s parents.